Personal Saving: A Time Series Analysis of Three Measures of the Same Conceptual Series - Taubman, Paul (The Review of Economics and Statistics, 1968)
goodness of fit when compared to the results of tests based on the Grant data. The coefficients show no irregularities and the second coefficient in A* has the correct sign although it is not significantly different from zero. The derived a, in Model B are inconsistent with the constraints (0 a. < 1) for which the Meiselman model was developed. Since ai = 0.920 and a2 = -0.402, the weights, Wj, explode to infinity which is of course impossible to rationalize. This highlights the necessity of imposing constraints on the parameters of the estimating equation. The linear restriction 2-r. + 7r2= 0 was rejected at the 1 per cent level but given the inco-nsistency of the estimates of ai it would be incorrect to consider this as evidence in favor of the two poles of opinion model. Comparing the two models, the Meiselman version gives a better fit in the case of model A and A*, but the model based on the traditional expectations function is distinctly better than the Meiselman version in the case of two poles of opinion. This superiority would undoubtedly be enhanced because constrained estimation of the Meiselman version of Model B would increase the difference in R2. To conclude, an alternative set of British data has been shown to be consistent with the models developed by Bierwag and Grove and there is no need to infer that the expectations mechanism in the United Kingdom differs from that in the United States. It must be emphasized, nonetheless, that the improved results for the British test have been obtained by resorting to data taken from a smoothed yield curve. Theoretical reasons must be advanced to justify the smoothing process if support for hypotheses can only be established by using smoothed data. The dangers of spurious correlations must not be discounted.